Failure analysis of surface defects on aluminium extrudates - Chong, Chee Hao (2020)
In this investigation, there are two different aluminium alloy (AA6005) extrudate profiles provided to investigate surface defects and seek for any solutions to eliminate or minimise the defects. There were two surface defects found on the extrudates which are pick-up defect and die line defect. Pick-up defect has a teardrop shape and die line defect has black line streak appearance. These defects may be influenced by exit temperature of extrudate, process parameters, die bearing condition and billet quality. Effects of extrusion process parameters on the extrusion process were studied through finite element method (FEM) as the extrusion process parameters have significant effect on the die bearing wear and surface finish of aluminium extrudate. Also, a subroutine that calculate die wear depth based on modified Archard’s wear model was developed and used to study die wear behaviour on the measured points. It is noted that the highest die wear depth is found at die bearing entrance, up to 63.18 % difference compared to lowest die bearing wear depth. This is due to largest billet deformation occurs in this area. Pick-up defect is temperature sensitive and extrudate’s exit temperature cannot exceed its eutectic point (555 ℃). Ram speed is suggested to reduce to below 3 mm/s or decrease initial billet temperature to below 480 ℃ according to the extrusion process parameters given by the company in order to ensure extrudate’s exit temperature is below its eutectic point. On the other hands, die line defect is mainly due to imperfections of die bearing surface. This defect can be minimised by reducing ram speed to below 3 mm/s or increasing initial billet temperature to above 480 ℃ according to the extrusion process parameters given by the company to reduce extrusion force to below 1452.582 tons which can decrease chances of spalling of nitriding layer. However, changing initial billet temperature can affect extrusion force which would affect die bearing wear and surface finish of aluminium extrudate. Die bearing condition and billet quality were not investigated in this research but re-nitriding and polishing of die and using better aluminium billet quality are suggested to eliminate or minimise both defects.